Apoptosis of peripheral blood lymphocytes in patients with juvenile idiopathic arthritis. Issue 8 (1st August 2003) - Smolewska, E; Brozik, H; Smolewski, P; Biernacka-Zielinska, M; Darzynkiewicz, Z; Stanczyk, J
Abstract : Background: Recent data suggested that abnormalities in mechanisms regulating apoptosis may have a role in the development of the rheumatoid process. Objective: To evaluate different aspects of apoptosis in children with juvenile idiopathic arthritis (JIA). Methods: The frequency of TUNEL positive peripheral blood (PB) lymphocytes (apoptotic index (AI)), as well as serum CD95 (APO1/Fas) antigen expression and serum levels of sFas and interleukin 15 (IL15), were examined in 44 cases of JIA. Results were correlated with type of onset, activity of JIA, and acute phase indicators. Results: The AI of lymphocytes was significantly higher in patients with JIA than in controls (p=0.020). The mean AI of lymphocytes was increased in JIA with systemic type of onset and high activity (p=0.001). Moreover, IL15 levels in systemic disease were higher than in controls (p=0.012). An increased AI correlated with raised IL15 (p=0.046), erythrocyte sedimentation rate (p=0.005) and C reactive protein (CRP; p=0.017). Additionally, correlation was found between IL15 and CRP levels (p=0.039). CD95 and sFas levels were unchanged compared with controls. Conclusion: PB lymphocytes of children with JIA have an increased tendency to undergo apoptosis. The degree of apoptosis depends on the type of onset and activity of JIA and correlates with serum levels of IL15. Further studies are needed to explain whether this is an epiphenomenon of the disease activity or is related to the pathogenesis of JIA.